Nilai-Nilai Pendidikan Karakter Bagi Anak Dalam Surah Ali Imron Ayat 79 - Mar’atun Nurul Solikhah; Maryono Maryono; Salis Irvan Fuadi (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2023)
This study aims to understand more deeply about the values ​​of character education in the Qur'an, especially in surah Ali Imron verse 79. In this study, researchers used qualitative research with a type of library research. As for the data collection technique through library research (library research), namely an analysis that the author uses by reading and studying some scientific literature that has something to do with the thesis to be studied. The results of this study indicate that the values ​​of character education contained in surah Ali Imron verse 79 are religious character education values ​​which have been applied and exemplified by Rasulullah saw as a caliph on this earth who has very good morals, and has the qualities a good character so that the miracles and advantages he possessed did not make the Messenger of Allah arrogant and did not make him belittle the oneness of Allah SWT.